(untitled) (Advancements in Homeopathic Research, 2022)
Anal fistula is one of the commonest problems to encounter in clinical practice. In conventional system of medicine, medication has a very limited role and surgery is the only option. This is the case of a patient presented with pain, offensive discharge and itching near anus for last three months. Afterwards he was diagnosed as a case of anal fistula on the basis of peculiar history and physical examinations. Treatment was started prospectively following strict homoeopathic principles and follow-ups done in suitable intervals for about 4months. A marked improvement was noted in the course of the treatment. Rationale of the case report is to show the effective management of such cases with proper homoeopathic treatment.